UNCOVERING THE POTENTIAL OF DIGITAL TAXATION: CHALLENGES AND OPPORTUNITIES IN THE AGE OF GLOBALIZATION - Loso Judijanto; Jackson Yumame; Aldrin Watson Gainau (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
It is hoped that the potential of a digital tax will provide a sense of justice, create a level playing field and healthy competition and increase economic growth. In the current era of the digital economy, countries with a high number of internet users such as Indonesia have to face many challenges. One of these challenges concerns digital taxes. Digital tax itself can generally be interpreted as a tax policy that is imposed or imposed on companies engaged in digital business globally. The toughest challenge in digitizing taxation is the quality of human resources. Ignorance or technology failure is a problem that must be overcome by the government so that this tax digitalization program is easy to implement. Tax digitalization is actually an initial step towards an increasingly improving economy while maintaining tax efficiency, transparency and fairness. This is to increase public awareness of taxes in order to achieve a stable economy. This research is research using the literature study method. This research discusses the definition of digital tax, the development of digital tax in the era of globalization, the challenges of digital tax, the benefits of digital tax for the government, the positive implications of digital tax for entrepreneurs, differences in regulations in various countries, compliance and supervision issues, collaboration between countries and digital tax system innovation.